FACTORS WHICH CAN ENHANCE OR WEAKEN LEVELS OF MOTIVATION OF EMPLOYEES IN AN ORGANISATION - SHONHIWA, BY DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This present paper attempts to discuss the various factors which either enhance or weaken levelsof motivation among employees in an organisation. It reveals that each employee has a differentset of factors that motivates him; her to do his/her best work. Owners of business and otheremployers need to understand what the motivations of workers are in order to effectively manageand grow a business that has the full support of its employees. Money is often the first factor tocome to mind, but successful entrepreneurs will see that as just one part of a larger picture ofincentives that drives employees to excel at their jobs. Motivating is critical in an organisation inthat it is next to directing / leading. Managers can motivate their subordinates while guidingthem. Motivating means encouraging people to take more initiative and interest in the workassigned. It is an art of getting things done willingly from others. Motivation avoids clashes andnon-cooperation and brings harmony, unity and co-operative outlook among employees.Managers have to work as motivators of their subordinates.